Glyphosate in food: A narrative review - Christelle Bou-Mitri; Sabine Dagher; Alaa Makkawi; Zaynab Khreyss; Hussein F. Hassan (Journal of Agriculture and Food Research)
Glyphosate, a widely used broad-spectrum herbicide, plays a crucial role in global crop production due to its effectiveness and low cost. This paper provides an updated overview of the exposure routes, regulations, occurrence, dietary exposure and risk characterization of glyphosate in food products worldwide in recent years. Glyphosate had been detected in various staple food products, including maize, wheat and soybeans, in regions such as Europe, Canada and USA. The herbicide was associated with cancer, reproductive disorders, and development defects. To address safety concerns, maximum residue limits (MRLs) for glyphosate have been established by several international agencies. Notably, no studies to date have reported exceedance of the acceptable daily intake (ADI), and all calculated hazard quotients (HQ) suggested a very low risk. This review highlights a research gap at the intersection of glyphosate use, climate change, and sustainability. It calls for examination of how evolving environmental conditions and agricultural practices might affect glyphosate application and its implications for food safety and public health.